What Is Cracow? A Semantic Field Analysis - Warmińska, Katarzyna; Urbaniak, Anna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
The article presents ways the inhabitants of Cracow define the city they live in. It is based on the results of qualitative research, elaborated using semantic field analysis of the term „Cracow”, which enabled us to show how people define Cracow, how they describe it, what they associate it with, what it is thought to stand against, what Cracow does and what can be done to Cracow.